Improved dynamics and gravitational collapse of tachyon field coupled with a barotropic fluid - Marto, João (2018)
We consider a spherically symmetric gravitational collapse of a tachyon field with an inverse square potential, which is coupled with a barotropic fluid. By employing an holonomy correction imported from loop quantum cosmology, we analyse the dynamics of the collapse within a semiclassical description. Using a dynamical system approach, we find that the stable fixed points given by the standard general relativistic setting turn into saddle points in the present context. This provides a new dynamics in contrast to the black hole and naked singularities solutions appearing in the classical model. Our results suggest that classical singularities can be avoided by quantum gravity effects and are replaced by a bounce. By a thorough numerical studies we show that, depending on the barotropic parameter $γ$, there exists a class of solutions corresponding to either a fluid or a tachyon dominated regimes. Furthermore, for the case $γ \sim 1$, we find an interesting tracking behaviour between the tachyon and the fluid leading to a dust-like collapse. In addition, we show that, there exists a threshold scale which determines when an outward energy flux emerges, as a non-singular black hole is forming, at the corresponding collapse final stages.